2017
DOI: 10.7752/jpes.2017.03205
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Abstract:Problem Statement: To date, most epidemiological studies on martial arts or combat sports have involved injuries incurred at the advanced or elite level. Thus far, there have been no studies on judo injuries sustained by students while participating in physical education classes. Purpose: The aim of this study was to assess the profile of injuries among physical education judo students and identify whether age and sex correlate with injuries. Approach: Male (n = 273) and female (n = 327) college stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…They have reported that the prevalence of injuries that occurred during the 2008 and 2012 Olympic Games was about 11-12%, which shows the high level of injury in this sport. Lariosa et al [4] reported that the Philippine student judo team from 2011 to 2016 had a total of 180 injuries with a rate of 9.4 per 1000 athletes exposed. Kim et al [5] also reported that South Korean Olympic judokas had at least four injuries per year.…”
Section: Introductionmentioning
confidence: 99%
“…They have reported that the prevalence of injuries that occurred during the 2008 and 2012 Olympic Games was about 11-12%, which shows the high level of injury in this sport. Lariosa et al [4] reported that the Philippine student judo team from 2011 to 2016 had a total of 180 injuries with a rate of 9.4 per 1000 athletes exposed. Kim et al [5] also reported that South Korean Olympic judokas had at least four injuries per year.…”
Section: Introductionmentioning
confidence: 99%
“…There has been much research conducted investigating the injuries that can occur in PE class or analyzing safety risk factors (Kelly, 1997;Lariosa et al, 2017;Severs, 2003). However, little research has been conducted to explore the perception and practice of safe PE classes from the perspective of PE teachers who teach students.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the back pain is a fairly common complaint of a large number both young (Patel, & Kinsella, 2017, Malkogeorgos, et al, 2011 and elite athletes (Lariosa, et al, 2017;De Luigi, 2014). It has been ANTON BOTOV, PAVEL SHNYAKIN, ALEKSANDER OSIPOV, TATYANA ZHAVNER -…”
Section: Introductionmentioning
confidence: 99%